Perlindungan Hukum terhadap Anak Sebagai Korban Tindak Pidana Pelecehan: Studi Kasus Pondok Pesantren Bani Ma’mun, Kabupaten Serang - Nurlaila Nurlaila; Mira Anjani; Putik Kasih S; Juheni Lalawaralata; Amalia Naura H; Tyara Maharani (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
Sexual harassment against children in Islamic boarding schools is a serious issue that demands special attention, particularly in the context of legal protection for victims. This study aims to analyze the position and role of child victims in the dynamics of sexual harassment crimes within pesantren, as well as to identify forms of legal protection that can be provided through a victimological approach. One of the cases highlighted in this research occurred at Bani Ma’mun Islamic Boarding School, located in Gembor Udik Village, Cikande Sub-district, Serang Regency, which illustrates the weak protection afforded to children in religious educational environments. By employing an empirical juridical method and referring to secondary data such as legislation, legal documents, and academic literature, this study finds that child victims often do not receive optimal protection, either in the criminal justice process or in terms of psychosocial support. The victimological perspective emphasizes the importance of fulfilling victims' rights, including the right to security, physical and mental rehabilitation, and social reintegration. In this context, protection efforts should not only focus on imposing sanctions on perpetrators but also include the formulation of policies oriented toward the recovery of victims. Therefore, this study recommends strengthening institutional capacity within pesantren to develop and implement comprehensive child protection mechanisms, including regulatory reform and more responsive law enforcement toward victims of sexual crimes. This research is expected to contribute to the development of a legal framework that is more victim-oriented within Indonesia’s criminal justice system.